The Effects of Education and Parents' Income on Interest in Continuing Strata-2 / S2 Santri in Islamic Boarding School Students Jagad 'Alimussirry Institutions - Faritz, Miftaqh Nur; Rahmatika, Resty (http://jagadalimussirry.com/, 2020)
Abstract. This research aims to analyze the role of parental education and parental income in influencing the interest in continuing S2 students in Islamic boarding school Students Jagad Alimussirry. This type of research is associative quantitative research. The subjects of this study were students of Islamic boarding school Jagad Alimussirry force 2016-2017 who are currently studying S1 at State University of Surabaya amounting to 32 students. Data collection techniques using instruments in the form of a questionnaire. Data from this research are in the form of the results of the students' responses to the questionnaire which were analyzed using the normality test, linearity test, multicollinearity test, autocorrelation test and heterokesdasticity test for the prerequisite tests of analysis. As for the hypothesis test using the t test, f test, and the coefficient of determination test. From this research it was found that (i) The majority of santri parents 'education was in the junior high school level by 34.37% (ii) The majority of santri parents' income was in the medium position of 62,5%. (iii) F Test results show that the independent variables (X1 and X2) are greater than the error level of 5%. Based on the results of the study it can be concluded that the education and income of parents do not significantly influence the interest in continuing the study of S2 students in Islamic boarding school students Jagad Alimussirry.